2013
DOI: 10.1007/s12272-013-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

Sparstolonin B suppresses lipopolysaccharide-induced inflammation in human umbilical vein endothelial cells

Abstract: Sparstolonin B (SsnB) is an isocoumarin compound isolated from the tubers of both Sparganium stoloniferum and Scirpus yagara. We previously demonstrated that SsnB blocked the Toll-like receptor (TLR) 2- and TLR4-triggered inflammatory signaling in macrophages by inhibiting the recruitment of MyD88 to the TIR domains of TLR2 and TLR4. The present study was designed to examine the effects of SsnB on vascular inflammatory responses in human umbilical vein endothelial cells (HU-VECs) challenged by lipopolysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Previous phytochemical studies showed various phenol acids, cisstilbenoids, aromatic alkine and isocoumarin isolated from Scirpus yagara would be the effective constituents (Cui et al, 2012;Liang et al, 2013aLiang et al, , 2013b. In the present study, we identified the presence of eight major compounds (protocatechuic acid, vanillic acid, p-coumaric acid, ferulic acid, sciryagarol I, methyl-3,6-dihydroxy-2-[2-(2-hydroxyphenyl)-ethynyl] benzoate, SsnB and SanLeng diphenyllactone) in AF by HPLC analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous phytochemical studies showed various phenol acids, cisstilbenoids, aromatic alkine and isocoumarin isolated from Scirpus yagara would be the effective constituents (Cui et al, 2012;Liang et al, 2013aLiang et al, , 2013b. In the present study, we identified the presence of eight major compounds (protocatechuic acid, vanillic acid, p-coumaric acid, ferulic acid, sciryagarol I, methyl-3,6-dihydroxy-2-[2-(2-hydroxyphenyl)-ethynyl] benzoate, SsnB and SanLeng diphenyllactone) in AF by HPLC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified the presence of eight major compounds (protocatechuic acid, vanillic acid, p-coumaric acid, ferulic acid, sciryagarol I, methyl-3,6-dihydroxy-2-[2-(2-hydroxyphenyl)-ethynyl] benzoate, SsnB and SanLeng diphenyllactone) in AF by HPLC analysis. Among these, SsnB cannot only block monocyte/macrophage inflammatory responses mediated by TLR2 and TLR4, but also can attenuate inflammation in vascular endothelial cells (Liang et al, 2011(Liang et al, , 2013a(Liang et al, , 2013b. Ferulic acid inhibits LPS/IFN-γ-induced NF-κB activity which plays pivotal roles in the immediate-early stages of immune and inflammatory response (Ou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] TLRs play an essential part in the perception of microbes and shape the complex host responses that occur during infection. 4 However, the signalling initiated by TLRs is a double-edged sword since a prolonged and exaggerated response can cause tissue and organ damage.…”
mentioning
confidence: 99%